Confronting Institutional Discrimination in a Color-Blind World - Silva, Eric O.; Gillmann, Christopher J.; Tate, KeyAnna L. (Qualitative Sociology Review, 2018)
This article builds on the scholarship on color-blind ideology by examining discourse challenging two cases of institutional discrimination (the criminalization of unauthorized immigrants and sports teams’ use of Native American symbolism). Our research questions are first, what general options do anti-racists have for navigating norms of color-blindness in the public sphere? Second, how does context influence how people confront institutional discrimination? Based on an ethnographic content analysis of 165 letters to the editor published in American newspapers, we find that opponents of institutional discrimination have the choice of addressing one of four laminations. In each lamination, authors acknowledge framings of racial discrimination that are unacknowledged in previous ones. In the abstraction lamination, authors do not recognize race and ethnicity. In the pigmentation lamination, authors identify race and ethnicity, but not discrimination. Authors in the discrimination lamination acknowledge the practice is harmful to a particular racial or ethnic group, and the contextualization lamination lends added dimensionality to the discourse. A comparison of the laminations of pro-immigrant and anti-mascot letters demonstrates varying willingness to acknowledge racial discrimination. Namely, the pro-immigrant discourse was more color-blind than anti-mascot criticism. We consider the potential causes of these findings and offer suggestions for future research in the conclusion